Workplace Environment and Its Impact on Employee’s Performance in Nepalese Commercial Banks - Goet, Joginder (The EFFORTS, Journal of Education and Research, 2022)
The purpose of the study is to examine the influence of workplace environment on employees’ performance of Nepalese commercial banks. A well-structured questionnaire was developed to collect data from 240 respondents using purposive sampling technique. Data analysis was done using Statistical Packages for the Social Sciences (SPSS) to generate mean, standard deviation, correlation, and regression analysis, and to diagnose the collected data. The results revealed that there is a significant influence of Job Aids (JA), Team Effort (TE), Physical Environment (PE) and Supervisor Support (SS) on Employee’s Performance (EP) in Nepalese commercial banks. Furthermore, JA and PE have strong impact on Employee’s Performance and TE and SS have the least influence. The practical implications are transparent for the managers and employers in Nepalese commercial banks since the workplace environment helps to improve the performance of the employees. The originality lies in the article claiming to enhance the performance of the employees, the implementation of good workplace environment must be complemented.